Aplikasi Tracking Berkas (Studi Kasus: Berkas Pelayanan PBBP2 di Badan Pendapatan Daerah Kota Batam) - Metta Santiputri; Erna Nadira (ABEC Indonesia, 2022)
Regional Revenue Agency Batam City has the task of carrying out regional authority in themanagement of regional original income, regional tax revenues, regional levies, BUMD profits and otherlegitimate income. In order to achieve the objectives of the Batam City Bapenda, which is to realize accountableand transparent financial and regional wealth management, the Batam City Bapenda has prepared a strategy thatis to perfect tax regulations or regulations, especially to increase local tax revenues, improve local revenuemanagement facilities, and fulfill a tax system that accountable and transparent. A structured tax system andgood service help Batam City Bapenda in carrying out its duties and authorities. In the service flow, the runningof a file takes a long time, because it requires confirmation from several fields in the Batam City Bapenda. Theservices that enter the Batam City Bapenda are approximately 20 files a day, this happens periodically, so thatthe tax authorities often find out about the existence of a service file and many files are lost due to not runningone service flow. So, we need a PBB-P2 Service File Tracking System which is implemented with a web-basedcomputer. The application is built using the Prototyping research method, and produces applications that can beused by the Batam City Bapenda to overcome various existing problems.